Zinc oxide nanoparticles, preparation method thereof and acne removal, anti-inflammatory and oil control application thereof
By modifying zinc oxide nanoparticles by hyaluronic acid, the toxicity problem caused by acid sensitivity during external use of zinc oxide is solved, and the acid stability and biocompatibility are achieved, which significantly improves its acne removal and anti-inflammatory properties. , oil control treatment effect, while ensuring safety.
Patent Information
- Application Number
- CN202411638304.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-16
- Publication Date
- 2025-02-14
AI Technical Summary
There is a contradiction between efficacy and toxicity in the external application of zinc oxide, which is difficult to effectively solve the problem of skin toxicity caused by its acid sensitivity.
The zinc oxide nanoparticles are modified by hyaluronic acid to improve their acid stability and biocompatibility, and HA-ZnO nanoparticles are formed. The nanoparticles are prepared by ultrasonic or stirring treatment of water-soluble zinc salt and hyaluronic acid in water, and are spindle-shaped and have a particle size of 120-500 nm.
HA-ZnO nanoparticles not only have better acid stability and lower cytotoxicity, but also can specifically kill acne pathogens, showing good acne removal, anti-inflammatory, oil control effects, and high safety.
Smart Images

Figure CN119424251A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of nanomaterials and nanobiomedicine, and in particular to zinc oxide nanoparticles and a preparation method thereof, and their applications in removing acne, resisting inflammation and controlling oil. Background Art
[0002] In recent years, functional non-antibiotic skin care products have developed rapidly. Zinc oxide has been used in the treatment of various skin diseases such as erythema, eczema, skin ulcers and burns due to its broad-spectrum antibacterial activity and multiple skin regulating effects. Related products include zinc oxide ointment, calamine lotion, sulfonamide zinc oxide ointment and norfloxacin zinc cream. Studies have shown that the antibacterial activity of zinc oxide mainly comes from its physical contact with bacteria and photocatalysis, while its regulating effect on the skin depends on the release of zinc ions, such as inhibiting oil secretion, preventing and treating hair follicle keratinization, and promoting epithelial tissue repair. That is, the antibacterial effect is exerted in the form of zinc oxide, and the skin regulating effect is due to the presence of zinc ions. The physiological pH value of the normal human skin surface is acidic, so zinc oxide, as an acid-sensitive material, is easily degraded during skin application, resulting in the release of a large amount of zinc ions, thereby causing skin toxicity and skin redness. Therefore, there is a contradiction between the efficacy and toxicity of zinc oxide during skin external application, and there is no effective solution. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a hyaluronic acid-modified zinc oxide nanoparticle, a preparation method thereof, and acne-removing, anti-inflammatory and oil-controlling applications. The zinc oxide nanoparticles modified with hyaluronic acid not only have better acid stability and lower cytotoxicity, but also have a specific killing effect on acne pathogens. When applied to the skin, they can have good acne-removing, anti-inflammatory and oil-controlling effects.
[0004] The first aspect of the present invention provides a zinc oxide nanoparticle, wherein the zinc oxide nanoparticle is modified with hyaluronic acid and is prepared by treating a water-soluble zinc salt and hyaluronic acid in water by ultrasonic or stirring.
[0005] As a further improvement of the above solution, the zinc oxide nanoparticles are spindle-shaped and have a particle size of 120-500 nm.
[0006] As a further improvement of the above solution, the particle size of the zinc oxide nanoparticles is 150-300 nm.
[0007] As a further improvement of the above scheme, the feed ratio of the water-soluble zinc salt to hyaluronic acid is 1 mmol:(0.1-1 g), preferably 1 mmol:0.4 g.
[0008] As a further improvement of the above scheme, the water-soluble zinc salt can be various inorganic zinc salts and organic zinc salts, such as ZnCl 2 、ZnSO4 、Zn(CH 3 COO 2 、Zn(NO 3 ) 2 、ZnCO 3 、Zn 3 (PO 4 ) 2 、ZnBr 2 、Zn(C 6 H 11 O 7 ) 2 etc., preferably Zn(CH 3 COO 2 、Zn(NO 3 ) 2 、ZnSO 4 etc., and the most preferred is Zn(CH 3 COO 2 .
[0009] As a further improvement of the above solution, the concentration of the hyaluronic acid in water is 50-500 μg / mL.
[0010] The second aspect of the present invention provides a method for preparing zinc oxide nanoparticles as described in any one of the first aspects, comprising the following steps: Zn(CH 3 COO 2 The zinc oxide nanoparticles modified with hyaluronic acid are mixed in water, wherein the concentration of the hyaluronic acid in the water is 100-300 μg / mL, and then stirred at 70-90° C. for 1-5 min, the pH is adjusted to alkaline and subjected to ultrasonic or stirring treatment, wherein the ultrasonic or stirring treatment time does not exceed 10 min, and then stirred at room temperature for 1-3 h to obtain zinc oxide nanoparticles modified with hyaluronic acid.
[0011] It is understood that the alkalinity can be adjusted by using an inorganic base, such as NaOH, or an organic base, such as DEA.
[0012] As a further improvement of the above scheme, the ultrasonic treatment time is 2-8 minutes.
[0013] The third aspect of the present invention provides a use of the zinc oxide nanoparticles as described in any one of the first aspect or the zinc oxide nanoparticles prepared by the preparation method described in any one of the second aspect in preparing an external preparation with acne-removing effect.
[0014] The fourth aspect of the present invention provides a use of the zinc oxide nanoparticles as described in any one of the first aspect or the zinc oxide nanoparticles prepared by the preparation method described in any one of the second aspect in preparing an external preparation with anti-inflammatory effect.
[0015] A fifth aspect of the present invention provides a use of the zinc oxide nanoparticles as described in any one of the first aspect or the zinc oxide nanoparticles prepared by the preparation method described in any one of the second aspect in preparing an external preparation with oil-controlling effect.
[0016] As a further improvement of the above scheme, the external preparation is an external gel.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] Based on the bionic mineralization strategy, hyaluronic acid and water-soluble zinc salt are used as raw materials to solidify and synthesize hyaluronic acid-modified zinc oxide nanoparticles (HA-ZnO nanoparticles) in aqueous solution. The nanoparticles are spindle-shaped with a particle size of 120-500nm. After being made into a topical gel, it not only has the effect of removing acne, but also can selectively kill pathogens during the treatment process, reducing the impact on the skin microecology, and at the same time has the effects of anti-inflammatory, oil control, promoting epidermal repair, and preventing scar formation.
[0019] In terms of acne removal, HA-ZnO nanoparticles can accumulate in the skin under the action of hyaluronic acid and slow down their degradation rate in an acidic environment, thereby ensuring the antibacterial effect of the nanoparticles on Propionibacterium acnes in the skin; moreover, HA-ZnO nanoparticles can also induce the active aggregation of Propionibacterium acnes, enhance the penetration of nanoparticles into Propionibacterium acnes and upregulate the expression of its CPA42_RS11340 gene (polysaccharide deacetylase family), further enhancing the adhesion of Propionibacterium acnes to the nanoparticles. The penetrated nanoparticles can kill pathogens through multiple pathways such as inducing oxidative stress and affecting the metabolism of Propionibacterium acnes, thereby achieving the effect of acne removal.
[0020] In terms of anti-inflammatory, Propionibacterium acnes will stimulate skin cells to secrete pro-inflammatory factors, while HA-ZnO nanoparticles can significantly reduce the protein expression levels of pro-inflammatory factors such as TNF-α and IL, play a significant anti-inflammatory role, and promote the rapid healing of acne; in terms of oil control, HA-ZnO nanoparticles have a good retention effect in oily skin, and can inhibit the secretion of oil by sebaceous gland cells, unclog hair follicles and destroy the local hypoxic microenvironment, thereby inhibiting bacterial proliferation and promoting the recovery of skin in acne-damaged areas, forming a virtuous circle for the treatment of acne-related oily skin.
[0021] At the same time, HA-ZnO nanoparticles have little killing effect on skin probiotics Staphylococcus epidermidis, and can promote the diversity of colonized bacteria on the skin surface and the maintenance of skin homeostasis. HA-ZnO nanoparticles can also promote the proliferation and migration of fibroblasts, and promote the repair of skin after bacterial infection. In addition, in vivo experiments have also proved that the acne symptoms of mice subsided quickly after treatment with HA-ZnO nanoparticle gel, and no obvious skin side effects were observed; zebrafish and HET-CAM experiments also confirmed the excellent biocompatibility and non-irritation of HA-ZnO nanoparticles, indicating that HA-ZnO nanoparticles have good acne removal, anti-inflammatory, and oil control effects, and are highly safe. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 TEM image and lattice image of HA-ZnO nanoparticles;
[0024] Figure 2 is the particle size distribution diagram of HA-ZnO nanoparticles;
[0025] Figure 3 The UV-visible absorption spectra (A) and infrared absorption spectra (B) of HA-ZnO nanoparticles and ZnO nanoparticles;
[0026] Figure 4 The particle size of HA-ZnO nanoparticles prepared with different HA concentrations;
[0027] Figure 5 The particle size of HA-ZnO nanoparticles prepared with different ultrasonic treatment times;
[0028] Figure 6 The TEM morphology comparison results of HA-ZnO nanoparticles and ZnO nanoparticles;
[0029] Figure 7 The effect of nanoparticles on the turbidity of Propionibacterium acnes under different pH conditions;
[0030] Figure 8 The effect of different concentrations of nanoparticles on the turbidity of Staphylococcus epidermidis;
[0031] Fig. 9 ZnO nanoparticles and HA-ZnO nanoparticles at different pH 2+ Release conditions;
[0032] Fig.10 For different concentrations of Zn 2+ and the effect of HA on the turbidity of P. acnes ;
[0033] Fig.11 is the fluorescence intensity corresponding to intracellular ROS after treatment with different nanoparticles;
[0034] Fig.12 The antibacterial activity of HA-ZnO nanoparticles protected by NAC;
[0035] Fig.13 Microscopic observation of Propionibacterium acnes before and after inactivation by HA-ZnO nanoparticles;
[0036] Fig.14 The particle size distribution (A) and ζ potential change (B) of HA-ZnO nanoparticles before and after hyaluronidase treatment;
[0037] Fig.15 Effects of HA-ZnO nanoparticles on bacterial turbidity of Propionibacterium acnes (A) and Staphylococcus epidermidis (B) before and after hyaluronidase treatment;
[0038] Fig.16 The SEM results (A) and TEM results (B) of Propionibacterium acnes cells after treatment with HA-ZnO nanoparticles;
[0039] Fig.17 The cytotoxicity of HA-ZnO nanoparticles and ZnO nanoparticles at different concentrations on HSF cells (A) and HaCaT cells (B);
[0040] Fig.18 The release of Zn from HA-ZnO nanoparticles and ZnO nanoparticles in cells 2+ How levels change over time;
[0041] Fig.19 The results of plate cloning of HSF cells after treatment with HA-ZnO nanoparticles and ZnO nanoparticles;
[0042] Fig. 20 The migration images of HSF cells after treatment with HA-ZnO nanoparticles and ZnO nanoparticles and their relative migration levels;
[0043] Fig.21 The immunofluorescence imaging results of intracellular TNF-α after treatment with HA-ZnO nanoparticles and ZnO nanoparticles;
[0044] Fig. 22 The results of oil red staining of HA-ZnO nanoparticles and ZnO nanoparticles on the oil secretion of sebaceous gland cells;
[0045] Fig.23 The intradermal retention of HA-ZnO nanoparticles and ZnO nanoparticles in normal skin and oily skin;
[0046] Fig.24 The intradermal retention of HA-ZnO nanoparticles and ZnO nanoparticles in different skin layers of normal skin and oily skin;
[0047] Fig.25 The changes in acne morphology of mice in each group during the treatment process;
[0048] Fig.26 The relative area changes of acne in each group of mice;
[0049] Fig. 27 The results of H&E staining of the skin at the acne site of mice in each group;
[0050] Fig.28 The immunofluorescence imaging results of TNF-α, IL-8 and MMP2 in the skin of acne sites of mice in each group;
[0051] Fig.29 is the expression level of TNF-α, IL-8 and MMP2 in the skin of acne sites of mice in each group;
[0052] Fig.30 This is the morphology of mouse skin acne after 3 days of treatment;
[0053] Fig.31 The results of plating the homogenate of skin tissue from the acne area of mice after 3 days of treatment;
[0054] Fig.32 The acute toxicity results of HA-ZnO nanoparticles and ZnO nanoparticles on zebrafish embryos;
[0055] Fig.33 The development of zebrafish embryos after treatment with HA-ZnO nanoparticles and ZnO nanoparticles;
[0056] Fig.34 These are the irritating results of HA-ZnO nanoparticles and ZnO nanoparticles on blood vessels. DETAILED DESCRIPTION
[0057] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0058] The weight of the relevant components mentioned in the embodiments of the present invention description can not only refer to the specific content of each component, but also represent the proportional relationship of the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present invention description is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present invention description. Specifically, the mass described in the embodiments of the present invention description can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0059] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0060] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0061] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0062] Example 1
[0063] Prepare 10mmol / L Zn(CH 3 COO 2 Solution: Ultrapure water dissolves Zn(CH 3 COO 2 After solidification, ultrasonic cleaning was performed for 10 min in an ultrasonic cleaner and oscillated in a vortex mixer for 2 min to obtain Zn(CH 3 COO 2 The solution is ready for use.
[0064] Prepare 20 mg / mL HA solution: Mix 7000Da HA with ultrapure water to prepare HA solution for later use.
[0065] In a 50 mL round-bottom flask, add appropriate amount of ultrapure water, 1 mL of 10 mmol / L Zn(CH 3 COO 2The solution and 200 μL of HA solution with a concentration of 20 mg / mL, the total volume of the solution in the round-bottom flask is 20 ml, and the final concentration of HA is 200 μg / mL. The round-bottom flask is placed on a vortex mixer for mixing, and then placed in a constant temperature water bath at 80°C for magnetic stirring for 3 minutes; then, under the ultrasonic action of an ultrasonic cleaner, 400 μL of NaOH solution with a concentration of 100 mmol / L is added to the round-bottom flask, the pH is adjusted to alkaline, and ultrasonic treatment is performed for 5 minutes. After the ultrasonic treatment, stirring is continued at room temperature for 2 hours, and then centrifuged at 15000 rpm for 15 minutes, the supernatant is discarded, and it is re-dissolved with ultrapure water to obtain a hyaluronic acid-modified zinc oxide nanoparticle (HA-ZnO) solution.
[0066] The HA-ZnO nanoparticles obtained in Example 1 were analyzed and tested, and the TEM results were as follows: Figure 1 As shown, the particle size distribution Figure 2 The results show that HA-ZnO nanoparticles are spindle-shaped with a lattice spacing of 0.26nm, which points to the ZnO (002) lattice plane; the particle size distribution is uniform, with a lateral diameter of 228±3nm, mainly in the range of 120-300nm.
[0067] EDS elemental analysis results show that the nanoparticles mainly contain C, N, O, Zn and other elements, among which C and N elements mainly come from HA. Line scan results show that the HA signal is mainly distributed on the ZnO surface. When scanning into the nanoparticles to about 50nm, the HA signal drops sharply and the Zn element signal intensity gradually increases; point scan results also prove that HA-ZnO nanoparticles are mainly composed of C, N, O, Zn and other elements. UV-visible absorption spectrum Figure 3 As shown in A, there are obvious ZnO characteristic absorption peaks at 365.5nm and 386.5nm in the spectrum, and the characteristic absorption peak of HA-ZnO nanoparticles has a significant blue shift due to the presence of HA. Figure 3 As shown in B, HA-ZnO nanoparticles have a wavelength of about 3430 cm -1 The characteristic absorption peak of hydroxyl group is shown at 900~1800cm -1 The wavenumber range shows characteristic absorption peaks of glycosidic bonds, amide groups, carbonyl groups and other functional groups, about 510 cm -1 The characteristic absorption peak of Zn-O appears at
[0068] The above results confirmed the successful synthesis of ZnO nanoparticles and the surface modification of HA.
[0069] Example 2
[0070] The volume of the HA solution was replaced with 50 μL, the final concentration of HA was 50 μg / mL, and the remaining step parameters were the same as in Example 1 to obtain a HA-ZnO nanoparticle solution.
[0071] Example 3
[0072] The volume of the HA solution was replaced with 100 μL, the final concentration of HA was 100 μg / mL, and the remaining step parameters were the same as in Example 1 to obtain a HA-ZnO nanoparticle solution.
[0073] Example 4
[0074] The volume of the HA solution was replaced with 500 μL, the final concentration of HA was 500 μg / mL, and the remaining step parameters were the same as in Example 1 to obtain a HA-ZnO nanoparticle solution.
[0075] Example 5
[0076] The ultrasonic treatment time was adjusted to 2 min, and the remaining step parameters were the same as in Example 1 to obtain a HA-ZnO nanoparticle solution.
[0077] Example 6
[0078] The ultrasonic treatment time was adjusted to 8 min, and the remaining step parameters were the same as in Example 1 to obtain a HA-ZnO nanoparticle solution.
[0079] Example 7
[0080] The ultrasonic treatment time was adjusted to 10 min, and the remaining step parameters were the same as in Example 1 to obtain a HA-ZnO nanoparticle solution.
[0081] Comparative Example 1
[0082] In a 50 mL round-bottom flask, add appropriate amount of ultrapure water, 1 mL of 10 mmol / L Zn(CH 3 COO 2 The solution and 200 μL ultrapure water, the total volume of the solution in the round-bottom flask is 20 ml, and then it is placed in a constant temperature water bath at 80°C and magnetically stirred for 3 minutes; then, under the ultrasonic action of an ultrasonic cleaner, 400 μL of 100 mmol / L NaOH is added to the round-bottom flask, the pH is adjusted to alkaline, and ultrasonic treatment is performed for 5 minutes. After the ultrasonic treatment, stirring is continued at room temperature for 2 hours, and then centrifuged at 15000 rpm for 15 minutes. The supernatant is discarded and re-dissolved with ultrapure water to obtain a HA-ZnO nanoparticle solution with a HA content of 0.
[0083] Comparative Example 2
[0084] In a 50 mL round-bottom flask, add appropriate amount of ultrapure water, 1 mL of 10 mmol / L Zn(CH 3 COO 2The solution and 200 μL of HA solution with a concentration of 20 mg / mL, the total volume of the solution in the round-bottom flask is 20 ml, and the final concentration of HA is 200 μg / mL. The round-bottom flask is placed on a vortex mixer for mixing, and then placed in a constant temperature water bath at 80°C for magnetic stirring for 3 minutes, and then 400 μL of NaOH solution with a concentration of 100 mmol / L is added to the round-bottom flask, the pH is adjusted to alkaline, and stirring is continued at room temperature for 2 hours, and then centrifuged at 15000 rpm for 15 minutes, the supernatant is discarded and re-dissolved with ultrapure water to obtain HA-ZnO nanoparticle solution.
[0085] Test Example 1: Effects of HA concentration and ultrasonic treatment time on the particle size of HA-ZnO nanoparticles
[0086] The particle size of the HA-ZnO nanoparticles obtained in Examples 1-4 and Comparative Example 1 was measured. The effect of HA concentration on the formation of HA-ZnO nanoparticles is shown in the figure. Figure 4 The results show that when there is no HA in the system, the size of the formed nanoparticles is greater than 1000nm; as the HA concentration increases, the size of the nanoparticles gradually decreases, and reaches a minimum value of about 280nm when the HA concentration is 200μg / mL; and when the HA concentration continues to increase, the size of the nanoparticles begins to increase again.
[0087] The particle size of the HA-ZnO nanoparticles obtained in Example 1, Examples 5-7 and Comparative Example 2 was measured. The effect of ultrasonic treatment on the formation of HA-ZnO nanoparticles is shown in FIG. Figure 5 The results show that when there is no ultrasound assistance during the synthesis of nanoparticles, the solution has no obvious characteristic opalescence of nanoparticles, and the particle size is about 400nm; when ultrasound-assisted treatment is used, the size of the synthesized nanoparticles first gradually decreases and reaches a minimum value, and then begins to gradually increase as the ultrasound treatment time increases.
[0088] Example 8
[0089] In a 5L reaction bottle, add appropriate amount of ultrapure water, 150mL of 10mmol / L Zn(CH 3 COO 2 The solution and 20 mL of HA solution with a concentration of 20 mg / mL were stirred evenly, and the total volume of the solution in the reaction bottle was 2 L. The reaction bottle was placed in a 70°C constant temperature water bath and magnetically stirred for 5 min, and then 50 mL of NaOH solution with a concentration of 100 mmol / L was added and stirred for 6 min, and then continued to stir at room temperature for 3 h, filtered, washed, and dried to obtain HA-ZnO nanoparticles in a dry state, and the particle size was detected to be about 260 nm.
[0090] Next, the HA-ZnO nanoparticles obtained in Example 1 and common ZnO nanoparticles with similar particle sizes purchased from the market were tested to evaluate the effect of HA modification on various properties of ZnO nanoparticles.
[0091] Test Example 2: Comparison of physical and chemical properties between HA-ZnO nanoparticles and ordinary ZnO nanoparticles
[0092] The morphology difference between the HA-ZnO nanoparticles obtained in Example 1 and the common ZnO nanoparticles purchased from the market is as follows: Figure 6 As shown in the figure, the morphology of HA-ZnO nanoparticles is uniform and presents a spindle-shaped structure, while the morphology of ZnO nanoparticles is uneven and generally presents a short rod-shaped structure. From the physical and chemical properties of nanoparticles, the particle size of HA-ZnO nanoparticles is 276±14nm, PDI is 0.055, and ζ potential is -19.5±0.8mV, while the particle size of ZnO nanoparticles is 243±13nm, PDI is 0.304, and ζ potential is -11.7±0.1mV. The particle sizes of the two are similar, and the average lateral diameter of ZnO nanoparticles is slightly lower than that of HA-ZnO nanoparticles, but the dispersion coefficient of HA-ZnO nanoparticles is significantly lower than that of ZnO nanoparticles, indicating that HA-ZnO nanoparticles have better dispersion stability.
[0093] Test Example 3: Antibacterial activity detection of nanoparticles against Propionibacterium acnes
[0094] Acne, also known as acne, is called acne vulgaris in medical terms. It is a chronic inflammatory skin disease involving the hair follicles and sebaceous glands. Its main pathogen is Propionibacterium acnes (P. acnes). By examining the effect of HA-ZnO nanoparticles on P. acnes, the acne-removing effect of HA-ZnO nanoparticles can be preliminarily evaluated. Due to the activation of serine proteases in the skin of acne patients, desmosome core protein 1 is degraded, which eventually causes the pH of the skin surface of 77.5% of patients to rise from the normal 4 to 5.5 to 5.5 to 6.8. Taking P. acnes BNCC330605 as the test bacteria, the killing effect of HA-ZnO nanoparticles and ZnO nanoparticles on P. acnes under two conditions of pH 5.5 and 6.8 was examined to simulate the antibacterial activity of nanoparticles in the overall skin environment.
[0095] Effects of nanoparticles on the turbidity of Propionibacterium acnes bacteria Figure 7 The results of the gradient dilution experiment showed that under the condition of pH = 6.8, when the concentration of HA-ZnO nanoparticles was lower than 6μg / mL, the turbidity of Propionibacterium acnes increased slightly, indicating that the bacterial density and number increased, indicating that HA-ZnO nanoparticles had no inhibitory effect on Propionibacterium acnes at this time; when the concentration of HA-ZnO nanoparticles was higher than 14μg / mL, the turbidity of Propionibacterium acnes decreased significantly, and when the concentration was 28μg / mL, no obvious turbidity was observed with the naked eye.
[0096] When the environmental pH dropped to 5.5, the antibacterial activity of HA-ZnO nanoparticles against Propionibacterium acnes decreased compared with that at pH 6.8. Especially when the concentration was 14 μg / mL, HA-ZnO nanoparticles even promoted the growth of bacteria. This may be because the Zn released by HA-ZnO nanoparticles gradually disintegrated under slightly acidic conditions. 2+ As a trace element, it promotes bacterial proliferation. Combined with the plate coating results, the MIC / MBC of HA-ZnO nanoparticles under two pH conditions were 28μg / mL and 56μg / mL.
[0097] For ZnO nanoparticles, under the condition of pH = 6.8, no antibacterial effect was observed at a concentration of 14 μg / mL of ZnO nanoparticles. When the concentration was increased to 25 μg / mL, the antibacterial effect was obvious. When the pH dropped to 5.5, the antibacterial activity of ZnO nanoparticles against Propionibacterium acnes decreased significantly, and even at a concentration of 250 μg / mL, the bacteria could not be completely killed, and turbidity could still be observed to the naked eye.
[0098] Test Example 4: Antibacterial activity test of nanoparticles against Staphylococcus epidermidis
[0099] Staphylococcus epidermidis (S. epidermidis) is the most abundant colonizing bacteria in human skin. It has probiotic function and can prevent the colonization of pathogens. By examining the antibacterial effect of HA-ZnO nanoparticles on S. epidermidis, the effect of HA-ZnO nanoparticles on skin microecology in the process of acne removal can be evaluated. Using S. epidermidis BNCC330867 as the test bacteria, the effect of nanoparticles on the skin microenvironment was evaluated by examining the killing effect of two nanoparticles on S. epidermidis at different concentrations. The effect of nanoparticles on the turbidity of S. epidermidis bacteria is shown in Figure 2. Figure 8 As shown. The results of the gradient dilution experiment showed that when the concentration of HA-ZnO nanoparticles was lower than 56μg / mL, the activity of Staphylococcus epidermidis did not change significantly, but this concentration was the MBC of HA-ZnO nanoparticles against Propionibacterium acnes, indicating that the antibacterial activity of HA-ZnO nanoparticles was selective and could specifically kill Propionibacterium acnes, while having low toxicity to Staphylococcus epidermidis. When the concentration of HA-ZnO nanoparticles was further increased to 448μg / mL, Staphylococcus epidermidis could still maintain a survival rate of about 50%; in contrast, ZnO nanoparticles had a stronger killing effect on Staphylococcus epidermidis, and at a concentration of 62.5μg / mL, the bacterial activity could be reduced by more than 50%.
[0100] The above results show that compared with ordinary ZnO nanoparticles, HA-ZnO nanoparticles have better antibacterial activity against the pathogen Propionibacterium acnes, and have lower toxicity to the probiotic Staphylococcus epidermidis, indicating that HA modification can improve the selectivity of ZnO nanoparticles for pathogenic microorganisms and reduce the potential impact of the acne removal process on the skin microecology.
[0101] Test Example 5: Nanoparticles of Zn 2+ Release behavior detection
[0102] To evaluate Zn 2+ Effect of release on antimicrobial effect of Zn 2+ The release amount was used as an indicator to investigate the stability of HA-ZnO nanoparticles and ZnO nanoparticles under two pH conditions. Fig. 9 The results showed that under neutral conditions (pH = 6.8), both nanoparticles could maintain good stability and no Zn 2+ When the pH dropped to 5.5, both nanoparticles showed Zn 2+ The sudden release of ZnO nanoparticles was obvious. 2+ The release of ZnO nanoparticles reached 90%, and the acid stability of HA-ZnO nanoparticles was stronger, with ZnO nanoparticles only appearing in about 1.5 h. 2+ Release the platform, the release amount is about 60%.
[0103] Afterwards, Zn 2+ and the antimicrobial effects of free HA, such as Fig.10 The results show that within the tested concentration range, Zn 2+ Both HA and ZnO nanoparticles promoted the proliferation of Propionibacterium acnes, indicating that the antibacterial effect of HA-ZnO nanoparticles on Propionibacterium acnes is not due to the 2+ Instead of being released, the antibacterial effect is exerted in the form of nanoparticles.
[0104] Test Example 6: Detection of ROS Levels in Propionibacterium acnes
[0105] The DCFH-DA probe was used to evaluate the intracellular ROS level of Propionibacterium acnes after HA-ZnO nanoparticles and ZnO nanoparticles were treated in the dark, and the fluorescence intensity was quantitatively detected by an ELISA instrument. The results are shown in Fig.11 As shown in Figure 2, compared with ordinary ZnO nanoparticles, the bacteria treated with HA-ZnO nanoparticles showed more obvious fluorescence signals. By adding NAC (a strong antioxidant) to remove free radicals in the bacteria, the effect of HA-ZnO nanoparticles on the turbidity of Propionibacterium acnes under the protection of NAC is shown in Figure 2. Fig.12As shown, the results showed that NAC could completely reverse the antibacterial activity of HA-ZnO nanoparticles, indicating that the imbalance of intracellular oxidative stress levels of bacteria induced by HA-ZnO nanoparticles played an important antibacterial role.
[0106] Test Example 7: Aggregation effect of HA-modified nanoparticles on bacteria
[0107] like Fig.13 As shown, during the experiment, the applicant observed that Propionibacterium acnes showed abnormal aggregation after co-treatment with HA-ZnO nanoparticles, while this aggregation effect was not observed in the inactivated Propionibacterium acnes, indicating that this aggregation effect is a biological chemotaxis rather than a simple physical aggregation.
[0108] To verify whether this active chemotaxis is related to the HA modification on the surface of the nanoparticles, 125 μg / mL hyaluronidase (Hase) was used to treat the HA on the surface of HA-ZnO nanoparticles, and the changes in the physicochemical properties and antibacterial activity of HA-ZnO nanoparticles before and after hyaluronidase treatment were measured.
[0109] Changes in the physicochemical properties of HA-ZnO nanoparticles before and after hyaluronidase treatment Fig.14 As shown, Fig.14 A is the change of particle size, Fig.14 B is the change of ζ potential, and the change of antibacterial activity is as follows Fig.15 The results showed that after hyaluronidase treatment, the particle size, dispersion coefficient and ζ potential of the nanoparticles became smaller, and the killing activity against Propionibacterium acnes was significantly weakened, indicating that HA modification increased the affinity of ZnO nanoparticles for Propionibacterium acnes; while hyaluronidase treatment did not affect the killing effect of nanoparticles on Staphylococcus epidermidis, indicating that HA modification of HA-ZnO nanoparticles can make the nanoparticles selective in their antibacterial ability against pathogenic bacteria.
[0110] The commonly used treatment for acne is to use topical antibiotics, but their indiscriminate killing of Propionibacterium acnes and Staphylococcus epidermidis can easily lead to an imbalance of the commensal flora on the skin surface and cause a series of toxic side effects. The HA-modified ZnO nanoparticles provided by the present invention have a specific biological chemotactic effect on Propionibacterium acnes, can improve the acne removal effect, and reduce damage to skin probiotics.
[0111] Test Example 8: Effect of HA-ZnO nanoparticles on the morphology of Propionibacterium acnes
[0112] The bacterial suspension was exposed to HA-ZnO nanoparticles for 12 hours before sampling. After centrifugation, washing and fixation, SEM and TEM were used to visually observe the changes in the morphology of Propionibacterium acnes caused by HA-ZnO nanoparticles treatment.
[0113] SEM results are as follows Fig.16 As shown in A, the results show that the untreated Propionibacterium acnes has a complete cell morphology and a regular rod-like shape, while after treatment with HA-ZnO nanoparticles, the adhesion of nanoparticles can be observed on the surface of Propionibacterium acnes, and obvious wrinkles and bacterial ruptures appear on the surface of the bacteria.
[0114] The TEM results are shown in Figure 16B. The results show that after treatment with HA-ZnO nanoparticles, there was obvious nanoparticle adhesion around the bacteria, and the bacteria showed obvious separation of cell wall and cytoplasm, the integrity of the cell wall and cell membrane was damaged, and the cytoplasm was condensed and even leaked.
[0115] Test Example 9: Effect of HA-ZnO Nanoparticles on Propionibacterium acnes Genes
[0116] Transcriptome analysis of P. acnes treated with HA-ZnO nanoparticles showed that there were significant differences in gene expression between the HA-ZnO group (treated with HA-ZnO nanoparticles) and the control group (treated with PBS, Control), including 330 upregulated significantly differentially expressed genes (DEGs) and 328 downregulated DEGs. Cluster analysis of the top 35 DEGs subsequently showed that genes encoding key enzymes related to nitrogen metabolism and glycolysis in bacteria were significantly upregulated, including CPA42_RS11220, CPA42_RS11215, CPA42_RS06390, cobj and gap, but the gene CPA42_RS05085 encoding bacterial aerobic respiration-related enzymes was significantly downregulated, suggesting that the normal energy metabolism of bacteria was disrupted after HA-ZnO nanoparticle treatment, and the bacteria compensated for the energy deficiency caused by anaerobic respiration by degrading pyrimidine biochemical pathways. At the same time, genes encoding anti-oxidative stress-related pathways (CPA42_RS01705, CPA42_RS12270, CPA42_RS04765) were upregulated, but genes encoding key enzymes and proteins of the antioxidant system, CPA42_RS09675 (superoxide dismutase), CPA42_RS11265 (aldehyde-keto reductase) and trxA (thioredoxin), were significantly downregulated, suggesting that obvious oxidative stress occurred in the bacteria.
[0117] In addition, the expression of genes encoding bacterial cell wall synthesis (CPA42_RS11610, murQ) was abnormal, indicating that the integrity of the bacterial cell wall was impaired. The gene encoding phage shock protein (CPA42_RS09385) was upregulated, and the cell membrane-related gene (CPA42_RS02090, amaP) was downregulated, indicating that the integrity of the bacterial inner membrane and secretion function were impaired. Genes such as phoU, CPA42_RS09365, CPA42_RS02320 and CPA42_RS02660 in bacteria are related to ATP-binding cassette (ABC) transporters, phosphate transporters and MFS transporters, and their downregulation suggests that the material exchange or metabolic process of bacteria is weakened. This was also confirmed by the down-regulation of genes related to bacterial gene transcription and translation (CPA42_RS00995, CPA42_RS05525, CPA42_RS05405, CPA42_RS11290, CPA42_RS01960, CPA42_RS01555, CPA42_RS11420, CPA42_RS05880). The down-regulation of CPA42_RS04710 (MarR family transcription factor) and msrA genes, which are related to bacterial pathogenicity and drug resistance, indicated that HA-ZnO nanoparticles have the potential to effectively inhibit P. acnes and reduce its drug resistance. It is worth noting that the up-regulated CPA42_RS11340 gene is involved in the encoding of proteins related to the polysaccharide deacetylase family, which can deacetylate more -NH in the bacterial surface polysaccharides by exposing more -NH 2 Enhances bacterial adhesion.
[0118] To further clarify the effect of HA-ZnO nanoparticles on P. acnes, gene ontology enrichment analysis (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed on DEGs. GO analysis results showed that HA-ZnO nanoparticles significantly affected multiple molecular functions of bacteria, such as catalytic activity, binding, structural molecule activity, transporter activity, ATP-dependent activity, and transcriptional regulator activity, and thus significantly affected the expression of cellular components such as bacterial cell anatomical entities and protein-containing complexes, ultimately leading to abnormal biological processes such as bacterial growth, cellular processes, metabolic processes, biological regulation, and response to stimuli. KEGG analysis results also showed that HA-ZnO nanoparticles significantly affected bacterial carbon metabolism, ABC transporters, ribosomes, and oxidative phosphorylation, indicating that HA-ZnO nanoparticles significantly interfered with the normal synthesis, exchange, or metabolism of bacteria and the normal supply of energy. Moreover, HA-ZnO nanoparticles also significantly downregulated pathways related to combating oxidative stress, such as the pentose phosphate pathway, the two-component system, porphyrin and chlorophyll metabolism, and cysteine and methionine metabolism, suggesting a serious imbalance in the level of oxidative stress within bacterial cells.
[0119] Based on the above results, the antibacterial mechanism of HA-ZnO nanoparticles against Propionibacterium acnes can be summarized into three stages: first, targeted recognition, Propionibacterium acnes is induced by HA to actively approach HA-ZnO nanoparticles; second, adhesion and penetration, through positive and negative electrical attraction and adhesion, HA-ZnO nanoparticles are promoted to penetrate into cells, inducing a significant upregulation of the intracellular CPA42_RS11340 gene (polysaccharide deacetylase family), which inducing deacetylation of bacterial surface polysaccharides to expose more -NH 2 , making it adhere more tightly to the negatively charged nanoparticles, thereby enhancing the interference of HA-ZnO nanoparticles on bacteria; finally, to kill bacteria, HA-ZnO nanoparticles that penetrate into cells can induce intracellular oxidative stress and interfere with normal bacterial respiration, material exchange and metabolism, thereby inhibiting bacterial growth and even causing their death. Since the antibacterial action pathways of HA-ZnO nanoparticles are diverse, the emergence of bacterial resistance mechanisms can be avoided.
[0120] Test Example 10: Cytotoxicity Detection
[0121] Using HSF cells and HaCaT cells as models, the cell compatibility of HA-ZnO NPs and ZnO NPs was evaluated by MTT assay, as shown in Fig.17 The results showed that compared with ZnO nanoparticles, HA-ZnO nanoparticles had lower cytotoxicity, the cell survival rate within the dosage range was greater than 80%, and HA-ZnO nanoparticles at low concentrations also had a certain effect of promoting cell proliferation.
[0122] Test Example 11: Detection of intracellular ROS levels
[0123] HaCaT cells in the logarithmic growth phase were digested, counted, and plated, and then placed in a cell incubator for 24 hours. The waste liquid was discarded, and the cells were washed twice with sterile PBS. HA-ZnO nanoparticles and ZnO nanoparticle solutions were added respectively. After incubation at 37°C for 12 hours, the excess drugs were washed away in the same steps, and then 10 μmol / L DCFH-DA fluorescent probe was added to the corresponding wells of the well plate. The well plate was placed under an inverted fluorescence microscope to observe the fluorescence intensity of each group and the cell fluorescence intensity was detected by flow cytometry. The results showed that the intracellular ROS level was only slightly increased after the cells were treated with HA-ZnO nanoparticles, but a high level of ROS signals was detected in the cells after the ZnO nanoparticles were treated.
[0124] Test Example 12: Evaluation of Cellular Nanoparticle Uptake Ability
[0125] HaCaT cells growing in logarithmic growth were taken at 4×10 4The cells were inoculated at a density of 1000 cells / well in a 6-well plate and incubated overnight. HA-ZnO nanoparticles and ZnO nanoparticles were added at 20 μg / mL to intervene in the cells for 24 hours, then washed 3 times with PBS, digested with nitric acid overnight, and finally diluted 4 times with double distilled water and the Zn content was detected by ICP-OES. The results showed that there was no significant difference in the cellular uptake of HA-ZnO nanoparticles and ZnO nanoparticles by HaCaT cells.
[0126] Test Example 13: Intracellular Zn 2+ Release level detection
[0127] HaCaT cells in the logarithmic growth phase were digested and counted, and complete medium was added to make a single cell suspension, which was transferred to a 6-well plate with a seeding density of 2×10 4 The 6-well plate was placed at 37°C and 5% CO 2 After culturing in a constant temperature cell culture incubator for 24 h, HA-ZnO nanoparticles and ZnO nanoparticles were added to the system with a final concentration of 20 μg / mL (in terms of ZnO), and the cells were intervened for 0, 15, 30, and 60 min, respectively. After washing three times with sterile PBS, 30 μmol / L TTSQ probe was added to remove residual drugs, incubated at 37°C for 30 min, and then washed twice with sterile PBS. Images were taken under a fluorescence microscope at different time points, such as Fig.18 shown.
[0128] The results showed that after adding ZnO nanoparticles to the cells for 15 minutes, obvious Zn 2+ The signal increased significantly with the extension of time, while the intracellular Zn 2+ The signals were significantly lower than those in the ZnO nanoparticles treatment group.
[0129] Then, with the help of TPEN (a Zn 2+ Chelating agent) removes free Zn 2+ The results of MTT experiments showed that TPEN alleviated the toxicity of HA-ZnO nanoparticles and ZnO nanoparticles to HSF cells, indicating that the nanoparticles can effectively inhibit the toxicity of ZnO nanoparticles in HSF cells. 2+ Compared with ordinary ZnO nanoparticles, hyaluronic acid-modified ZnO nanoparticles can slow down the release of Zn 2+ release within the cell, thereby improving biosafety.
[0130] Test Example 14: Evaluation of the Proliferation and Migration Promoting Effects on Cells
[0131] The proliferation and migration effects of HA-ZnO nanoparticles and ZnO nanoparticles on HSF cells were investigated by plate cloning and scratch experiments, respectively. The plate cloning results of HSF cells treated with HA-ZnO nanoparticles and ZnO nanoparticles are shown in Figure 2. Fig.19 The migration images of HSF cells after treatment with HA-ZnO nanoparticles and ZnO nanoparticles and their relative migration levels are shown in Fig. 20 The results showed that HA-ZnO nanoparticles significantly promoted the proliferation of HSF cells and promoted the migration of HSF cells, while ZnO nanoparticles inhibited the proliferation and migration of cells, indicating that HA-ZnO nanoparticles also have certain skin repair potential and are expected to avoid the formation of acne scars.
[0132] Test Example 15: Anti-inflammatory Effect Evaluation
[0133] The anti-inflammatory effect of HA-ZnO nanoparticles was investigated at the cellular level. The results of cell immunofluorescence analysis were as follows: Fig.21 The results showed that after HaCaT cells were stimulated with Propionibacterium acnes, the expression of intracellular TNF-α protein increased significantly; after intervention with ZnO nanoparticles and HA-ZnO nanoparticles, the intracellular TNF-α protein was downregulated, and the anti-inflammatory effect of HA-ZnO nanoparticles was significantly better than that of ZnO nanoparticles, indicating that surface-modified hyaluronic acid has an important contribution to the enhancement of the anti-inflammatory activity of ZnO nanoparticles.
[0134] Test Example 16: Evaluation of the inhibitory effect on sebaceous gland cell oil secretion
[0135] Abnormal accumulation of cortex is an important cause of acne. Cortex can be used as a nutrient to promote the colonization and growth of Propionibacterium acnes. Excessive proliferation of Propionibacterium acnes will promote the synthesis of lipid droplets and triglycerides in skin sebaceous cells, leading to sebum aggregation and clogging of hair follicles, further aggravating local hypoxia, thereby promoting the growth of Propionibacterium acnes and forming a vicious cycle. By adding arachidonic acid (AA) to induce SZ95 human sebaceous gland cells to secrete oil, and using oil red to stain the oil, the effects of the two nanoparticles on the oil secretion of sebaceous gland cells are shown in Figure 2. Fig. 22 As shown, a is the oil secretion of the control group, b is the oil secretion of the cells after AA induction, c and d are the oil secretion of the cells after AA induction and addition of 20μg / mL and 40μg / mL ZnO nanoparticles, respectively, and e and f are the oil secretion of the cells after AA induction and addition of 20μg / mL and 40μg / mL HA-ZnO nanoparticles, respectively.
[0136] The results showed that after adding nanoparticles, the oil secretion of cells decreased to a certain extent, but compared with ZnO nanoparticles, the oil secretion of cells after adding HA-ZnO nanoparticles was significantly reduced. In addition, with the increase of nanoparticle concentration, the inhibitory effect of ZnO nanoparticles on oil secretion remained basically unchanged, while the inhibitory effect of HA-ZnO nanoparticles on oil secretion showed obvious dose dependence, indicating that the HA-ZnO nanoparticles prepared by the present invention can inhibit the secretion of skin oil, dredge hair follicles and destroy the local hypoxic microenvironment, thereby inhibiting the proliferation of bacteria and promoting the recovery of the skin in the damaged area of acne.
[0137] Test Example 17: In vitro skin model experiment
[0138] Animal and plant blended oils were used to simulate oily skin in acne conditions, and the penetration and retention abilities of HA-ZnO nanoparticles and ZnO nanoparticles in an in vitro skin model were investigated.
[0139] 2% Carbomer 941 gel was prepared. HA-ZnO nanoparticles and ZnO nanoparticles solutions were mixed with Carbomer gel at a ratio of 1:9 to form HA-ZnO gel and ZnO gel. The concentration of nanoparticles in the gel was 56 μg / mL (in terms of ZnO). Pig skin was used as a simulation object for in vitro transdermal and retention experiments. First, the pig skin was thawed at room temperature and cut into circles of the same size according to the shape of the Franz diffusion cell. Normal skin and oily skin were set up. Normal skin was smeared with physiological saline; oily skin was treated as follows: lard and vegetable oil were mixed in a mass ratio of 1:1 to form a blended oil, and 20 μL of the blended oil was evenly applied to the surface of the pig skin. After 5 minutes of absorption, the excess oil stains were wiped off and the operation was repeated twice. Then, the Franz diffusion cell was installed, and HA-ZnO gel and ZnO gel were evenly applied on the Franz diffusion cell. The instrument was turned on and the water bath was set to 32°C and 600rpm to start the experimental timing. Samples were taken at 0, 0.5, 1, 2, 4, 6, 8, and 12 hours, and the same volume of saline was used to supplement. After the last sampling time point, the stratum corneum and dermis of each group of pigskin were collected, and after digestion with aqua regia at 60°C for 24 hours, the samples were tested by ICP-OES.
[0140] The results showed that no Zn content was detected in the receiving pool at different time points, indicating that the nanoparticles can hardly penetrate the skin, avoiding the safety risk caused by excessive systemic zinc exposure. Fig.23As shown in the figure, there is no significant difference in the intradermal retention rate of ZnO nanoparticles in the two skin types, but the retention of HA-ZnO nanoparticles in oily skin is significantly higher than that in normal skin. In addition, the retention of HA-ZnO nanoparticles in normal skin is lower than that of ZnO nanoparticles, but the retention in oily skin is higher than that of ZnO nanoparticles, which is conducive to the enrichment of HA-ZnO nanoparticles in acne-affected areas and reduces irritation to normal skin.
[0141] The retention rates of the two nanoparticles in different structures of the skin were then analyzed, e.g. Fig.24 As shown. The results show that ZnO nanoparticles are more distributed in the dermis, while HA-ZnO nanoparticles are mainly distributed in the epidermis. Acne mainly occurs in the epidermis, which means that compared with ZnO nanoparticles, HA-ZnO nanoparticles can act more directly on the site of acne, improve the acne removal effect, and reduce unnecessary effects on deep tissues and reduce side effects.
[0142] Test Example 18: Mouse acne experiment
[0143] Healthy male BALB / c mice (6 weeks old, weighing 20-25 g) were used to construct an animal back skin acne model. The animals were purchased from Hunan Slake Jingda Experimental Animal Co., Ltd. and fostered in the Animal Experiment Center of Xiangya School of Medicine, Central South University (SPF grade). All animal experiments were conducted in accordance with the "National Laboratory Animal Management Regulations" and approved by the Animal Discipline Research Ethics Committee of Xiangya School of Pharmacy, Central South University (Ethics Review Number: XMXH--2023-1246).
[0144] Construction of mouse acne model: First, use a blade to remove the hair on the back of each mouse to form a patch of about 2×2 cm 2 Cultivate Propionibacterium acnes to the logarithmic growth phase and dilute the bacterial suspension to 5×10 8 CFU / mL. One day before the formal experiment, 50 μL of bacterial suspension was drawn into a syringe, and the bubbles in the syringe were removed. The suspension was then injected intradermally into the back of each mouse. The acne-affected areas and activity status of the mice were observed daily. The length (L) and width (W) of the skin acne area were measured with a vernier caliper, and the acne range area (A) was calculated according to the formula A=L×W.
[0145] Evaluation of anti-acne treatment effect: 24 hours after injection of Propionibacterium acnes, mice were randomly divided into 5 groups (n=6), and each mouse was marked with an ear tag and photographed. 50 μL of PBS or drug-containing gel was evenly applied once a day. The administration conditions of each group were (1) G1 group: PBS; (2) G2 group: erythromycin ointment; (3) G3 group: blank carbomer gel; (4) G4 group: ZnO gel; (5) G5 group: HA-ZnO gel. The size of skin acne was measured with a vernier caliper every day and photographed and recorded, and the skin acne area curve was calculated. After 7 days of administration, the mice were anesthetized with 1% pentobarbital, and the eye skin on the blood collection side was gently pressed to make the eyeball congested and protruding. The eyeball was clamped with elbow forceps and quickly removed. At the same time, the mouse heart was gently pressed with the middle finger of the left hand to speed up the heart pumping blood. After collecting the blood, it was centrifuged at 3500rpm for 10 minutes, and the serum was collected to detect liver and kidney indicators. The mice were killed by dislocation, and the skin tissues of the acne sites were removed by dissection. The levels of cytokines such as TNF-α, IL-8, and MMP2 in the skin tissues were evaluated using ELISA technology and immunofluorescence staining. Finally, the main organs of the mice were separated: heart, liver, spleen, lung, and kidney. Small parts of tissues from the same parts of the organs were uniformly cut and collected. The residual blood on the surface of the tissues was washed with PBS and then transferred to a sealed tube containing 4% paraformaldehyde for H&E staining.
[0146] Photos of mice with acne during treatment Fig.25 As shown, one day after intradermal injection of Propionibacterium acnes (Day 0), obvious acne-like protrusions formed at the injection site due to bacterial infection and proliferation, indicating the successful construction of a mouse acne model. Over time, although the acne area of the untreated G1 group tended to decrease, its edges gradually became clearer and the protrusions became more severe; after treatment with the positive control topical antibiotic ointment in the G2 group, the acne on the back of the mice significantly subsided until it disappeared on the 4th to 7th day, but the acne site showed obvious dryness, wrinkles and peeling, which may be due to skin irritation caused by topical erythromycin; there was no obvious change in the acne of the mice in the G4 group after treatment, indicating that the efficacy of the ZnO gel was poor; while the acne of the mice in the G5 group significantly subsided and the skin was smooth on the 3rd to 4th day of treatment, showing excellent anti-acne efficacy compared with the G3 and G4 groups. The changes in the relative area of acne in each group of mice are shown as follows Fig.26 As shown, the results are consistent with the treatment effects observed in the photographs.
[0147] On day 7, the mice were killed and the skin tissue from the acne site was isolated for histological and immunofluorescence analysis. Fig. 27H&E staining results showed that there were a large number of infiltrating inflammatory cells in the skin of G1, G3 and G4 groups, and the normal hair follicle structure of mice was destroyed, while the thickness of skin sections of G2 and G5 groups was significantly thinner than that of other groups, the infiltrating inflammatory cells in the skin were significantly reduced, and clear and complete dermis and reticular layer of hair follicle structure could be observed in the skin tissue, indicating that HA-ZnO nanoparticles have an anti-acne effect similar to that of topical erythromycin in vivo, while ZnO nanoparticles have no obvious therapeutic effect on acne.
[0148] Studies have shown that Propionibacterium acnes can stimulate keratinocytes in the epidermis to secrete cytokines such as TNF-α and IL-8, exacerbating inflammation in the acne area. TNF-α can further synthesize a large number of matrix metalloproteinases (MMPs) through the NF-κB signaling pathway, thereby affecting the normal production of collagen fibers and tissue healing and repair in the acne area, thereby promoting the formation of acne scars. The expression of related proteins in the acne area after treatment in different treatment groups was analyzed by immunofluorescence technology. The results of immunofluorescence imaging are shown in Figure 2. Fig.28 shown.
[0149] The results showed that compared with the G1 group, the expression of TNF-α, IL-8 and MMP-2 in the skin was significantly downregulated after G2 treatment; there was no significant difference between the G3 group and the G1 group, indicating that the blank carbomer gel had no effect on relieving acne; the G4 group only slightly reduced the expression of IL-8 and MMP-2 in the skin group after treatment; and the G5 group not only significantly reduced the expression of TNF-α, IL-8 and MMP-2 in the skin after treatment, but also had better effects than the G2 group. To further quantify the differences in protein expression in each group, the expression levels of each protein in the skin tissue homogenate of the mouse acne site were detected using an ELISA kit, such as Fig.29 As shown, the results were consistent with those of immunofluorescence.
[0150] To avoid individual differences, 5 acne models were created on the back of the same mouse. The skin conditions of each group were as follows 3 days after administration. Fig.30 The results showed that compared with group G1, the acne on the back of mice in groups G2 and G5 was significantly alleviated after treatment, but there was no therapeutic effect in groups G3 and G4.
[0151] Afterwards, the mice were euthanized, the mice were dissected, and the skin acne tissues were taken out and ground into a homogenate. The skin acne tissue homogenates of each group were dropped into fresh solid agar plates, and evenly spread with a plate spreader and then inverted. The solid agar plates were placed in a 37°C incubator for anaerobic culture for 24 hours, and the growth of the colonies was observed and photographed for record. Fig.31The results showed that after 3 days of treatment with different treatment methods, obvious bacteria were detected in the skin of groups G1, G3 and G4, but no obvious colony distribution was observed on the surface of the plates of groups G2 and G5, indicating that the antibacterial property of HA-ZnO nanoparticles was equivalent to that of erythromycin in the process of acne removal, while the antibacterial property of ZnO nanoparticles was poor.
[0152] Based on the above results, the topical gel made from HA-modified ZnO nanoparticles has multiple effects such as antibacterial and anti-inflammatory, inhibition of sebaceous gland oil secretion, and regulation of skin tissue structure. It has a more comprehensive acne-removing effect than topical antibiotics and has better safety.
[0153] Test Example 19: Zebrafish Embryo Safety Test
[0154] During the experiment of Test Example 18, the weight of mice in each group did not change significantly, indicating that HA-ZnO nanoparticles and ZnO nanoparticles had no serious toxic side effects on mice; there was no significant difference in liver and kidney indicators in the serum tests of mice in each group, indicating that the two nanoparticles did not cause serious damage to the liver and kidney organs; H&E staining results also proved that there was no obvious pathological damage to the main organs in each group, indicating that there were no obvious toxic side effects. The effect of hyaluronic acid modification on the safety of nanoparticles was further evaluated with the help of zebrafish model and HET-CAM chicken embryo chorioallantoic membrane test.
[0155] 2hpfAB strain wild-type zebrafish embryos (n=30) were taken, and HA-ZnO nanoparticles and ZnO nanoparticles were added to the embryos for 4 consecutive days. The embryos were photographed at 2, 48, 72 and 96hpf, and the mortality and deformity rates of the embryos were recorded. HPF is the abbreviation of hours post-fertilization, which is a time unit used to describe the development stage of zebrafish embryos, indicating the number of hours calculated from fertilization, such as 2hpf is 2 hours after fertilization.
[0156] The results of the acute toxicity experiment of nanoparticles on zebrafish embryos are as follows Fig.32 As shown in the figure, when zebrafish were exposed to 28 μg / mL ZnO nanoparticle solution, embryos died, and the embryo mortality rate reached about 20% after 48 hours; while the embryo mortality rate of zebrafish after intervention with the same concentration of HA-ZnO nanoparticles was about 6.67%. Fig.33 As shown in the results, ZnO nanoparticles delayed the hatching time of zebrafish embryos and caused deformities in zebrafish, such as pericardial cysts, but the above phenomenon was not seen in zebrafish treated with HA-ZnO nanoparticles. The above results show that HA-ZnO nanoparticles have better biocompatibility than ZnO nanoparticles.
[0157] Test Example 20: HET-CAM Chicken Embryo Chorioallantoic Membrane Test
[0158] The HET-CAM test was used to examine the irritation of different drug-containing gels to blood vessels and record the coagulation and rupture of blood vessels. The results are as follows: Fig.34 The results showed that there was bleeding in the blood vessels of the CAM membrane after treatment with ZnO nanoparticles, but no obvious changes were observed in the CAM treated with HA-ZnO nanoparticles, indicating that HA-ZnO nanoparticles are non-irritating to blood vessels and have excellent safety.
[0159] The present invention provides a hyaluronic acid-modified zinc oxide nanoparticle (HA-ZnO), which has stronger antibacterial activity against the pathogenic bacteria Propionibacterium acnes of acne, and has less lethality against the skin probiotic Staphylococcus epidermidis. Propionibacterium acnes has a biological chemotactic effect on HA-ZnO nanoparticles, which can make Propionibacterium acnes actively chemotactic to the surrounding of HA-ZnO nanoparticles, while Staphylococcus epidermidis, a normal colonizing bacteria of the skin, does not have this chemotactic effect, thereby improving the selectivity of nanoparticles for acne pathogens, reducing the potential impact on the skin microecology during the treatment process, and improving the therapeutic index. Moreover, the adhesion and penetration of HA-ZnO nanoparticles to Propionibacterium acnes can also promote the nanoparticles to enter the bacterial cell body. After entering the cell, the HA-ZnO nanoparticles can exert antibacterial effects by inducing intracellular oxidative stress and interfering with multiple mechanisms such as normal bacterial respiration, material exchange and metabolism, thereby avoiding drug resistance.
[0160] Hyaluronic acid modification can significantly enhance the acid stability of ZnO nanoparticles, reduce the release rate of zinc ions, improve biosafety, and inhibit the secretion of skin oil. Moreover, the slowly released zinc ions can promote the recovery of skin in acne-damaged areas from multiple angles, including promoting the migration and proliferation of fibroblasts to repair damaged skin in acne areas, and inhibiting keratinocytes from secreting inflammatory factors to relieve inflammation. Experiments on mouse acne models have confirmed the multiple therapeutic effects of HA-ZnO nanoparticles on acne treatment, and its therapeutic effect is better than that of positive drug erythromycin ointment, and its skin irritation is lower; in addition, zebrafish and chicken embryo chorioallantoic membrane tests have confirmed the improvement of the safety of ZnO nanoparticles by hyaluronic acid modification. The HA-ZnO nanoparticles provided by the present invention provide a new treatment strategy for the treatment of acne, and also provide new raw materials for the research and development of zinc oxide-based functional skin care products.
[0161] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A zinc oxide nanoparticle, characterized in that: The zinc oxide nanoparticles are modified with hyaluronic acid and are prepared by treating water-soluble zinc salt and hyaluronic acid in water through ultrasonic or stirring.
2. The zinc oxide nanoparticles according to claim 1, characterized in that The zinc oxide nanoparticles are spindle-shaped and have a particle size of 120-500 nm.
3. The zinc oxide nanoparticles according to claim 1, characterized in that The water-soluble zinc salt is ZnCl2, ZnSO4, Zn(CH3COO)2, Zn(NO3)2, ZnCO3, Zn3(PO4)2, ZnBr 2、 Zn(C6H 11 O7)2.
4. The zinc oxide nanoparticles according to claim 1, characterized in that The concentration of the hyaluronic acid in water is 50-500 μg / mL.
5. A method for preparing zinc oxide nanoparticles according to any one of claims 1 to 4, characterized in that: The following steps are involved: Zn(CH3COO)2 and hyaluronic acid are mixed in water, wherein the concentration of hyaluronic acid in water is 100-300 μg / mL, and then the mixture is placed at 70-90°C for reaction for 1-5 minutes, the pH is adjusted to alkaline, and ultrasonic or stirring treatment is performed, wherein the ultrasonic or stirring treatment time does not exceed 10 minutes, and then the mixture is stirred at room temperature for 1-3 hours to obtain zinc oxide nanoparticles modified with hyaluronic acid.
6. The method for preparing zinc oxide nanoparticles according to claim 5, characterized in that: The ultrasonic or stirring treatment time is 2-8 minutes.
7. Use of the zinc oxide nanoparticles according to any one of claims 1 to 4 or the zinc oxide nanoparticles prepared by the preparation method according to any one of claims 5 to 6 in preparing an external preparation having an anti-acne effect.
8. Use of the zinc oxide nanoparticles according to any one of claims 1 to 4 or the zinc oxide nanoparticles prepared by the preparation method according to any one of claims 5 to 6 in preparing an external preparation with anti-inflammatory effect.
9. Use of the zinc oxide nanoparticles according to any one of claims 1 to 4 or the zinc oxide nanoparticles prepared by the preparation method according to any one of claims 5 to 6 in preparing an external preparation with oil-controlling effect.
10. The use of zinc oxide nanoparticles according to any one of claims 7 to 9, characterized in that: The external preparation is an external gel.